RİNGER LAKTAT VE HES 200/0.5 SOLÜSYONLARI İLE SIVI REPLASMANININ ONKOTİK BASINÇ, OSMOLARİTE VE KOAGÜLASYON FAKTÖRLERİ ÜZERİNE ETKİLERİNİN KARŞILAŞTIRILMASI - DEMİROK, Mukadder and DİKMEN, Yalım and DEMİROLUK, İ. Şener and; HOĞLU, Ziya (Cerrahpaşa Medical Journal, 2014)
Background.- Comparison of effect of ringer lactate and 6 % HES 200/0.5 on osmolority, oncotic pressure and coagulation factors. Aim of our study is to compare the effects of crystalloid and colloid solutions which are used for replacement of blood and fluid loss, to plasma osmolority, oncotic pressure, urine osmolarity and coagulation factors. Design.- Forty-two patients who had abdominal surgery were included in our study. Standard anaesthesia was applied and ringer lactate was given as a maintenance fluid to all patients. Patients loses for the preparative period was calculated and replaced with the ringer lactate solution in the group 1 (crystalloid group) and 1/3 of the calculated volume with 6 % HES 200/0.5 in group 2 (colloid group). Intraoperative blood loss was replaced with Ringer Lactate in group I and 6% hydroxyethyl starch in group II. In group 1, the cristalloids were given three times the volume of blood loss. Blood samples were taken after intubation (A), at the end of the surgery (B) and postoperative 24th hour (C). Plasma oncotic pressure, osmolarity, arterial blood gases were measured in the blood samples and urine osmolarity was measured in the urine samples. Preoperative and postoperative 24th hour PT and aPTT values were measured too. Results.- There were no significant difference between two groups according to blood loss, urine volume, hemodynamics and blood gas measurements. Plasma osmolarity did not change in the crystalloid group. It was 295.2±8.8 and 302.6±8.8 for the period A and B, respectively in the colloid group (p<0.05). Oncotic pressure was changed in the crystalloid group. It was 20.1±2.7, 16.2±4.6 and 16.7±4.6 for the period A, B and C respectively (p<0.05).Oncotic pressure values were not changed in the colloid group. PT and aPTT values were not changed in crystalloid group. In the colloid group, at the beginning PT was 14.3±1.9 and aPTT was 30.4±7.6. At the postoperative 24th h measurement showed a significant rise, reaching the level PT 18.8±5.1 and aPTT 44.1±27.5 (p<0.05). Allergic reaction, pre-and postoperative abnormal bleeding and no hemodynamic complications were determined in the non of the groups. Conclusion.- Consequently, we can conclude that the blood loss replacement with 6% hydroxyethyl starch which provides volume replacement three times less volume according to crystalloid solutions, is safe and does not decrease oncotic pressure as crystalloid solutions do, so that colloid solutions could be used safely.